1997
DOI: 10.1021/ac9609081
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexation Reactions of Quinolone Antibiotics in a Quadrupole Ion Trap

Abstract: We have undertaken a systematic study of the nature of quinolone metal complexes formed by electrospray ionization and laser desorption/ion-molecule reactions to evaluate the analytical utility of metal complexation as an alternative to conventional ionization via protonation. Metal ionization with laser-desorbed copper and nickel ions results in addition products of the form (L + Cu+) and (L + Ni+), respectively, where L is the quinolone, whereas addition-elimination products of the form (L + Co(+)-28) are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 53 publications
2
48
0
4
Order By: Relevance
“…. In some cases, when Cu 2ϩ was used as a metal ion, CID spectra showed additional fragment ions [29,30]. The additional fragment ions derived from two dimeric fragment ions as a consequence of a loss of CO 2 , mainly from the [Cu…”
Section: Resultsmentioning
confidence: 99%
“…. In some cases, when Cu 2ϩ was used as a metal ion, CID spectra showed additional fragment ions [29,30]. The additional fragment ions derived from two dimeric fragment ions as a consequence of a loss of CO 2 , mainly from the [Cu…”
Section: Resultsmentioning
confidence: 99%
“…A number of groups have studied metal complexes by mass spectrometry and found that the fragmentation pathways of analytes can be significantly altered, allowing new opportunities for structural determination [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. The Brodbelt group has shown that metal complexation combined with the use of a neutral auxiliary ligand dramatically increases sensitivity for detection of flavonoids while also providing a richer array of fragments to aid in isomer differentiation [50 -52, 72].…”
mentioning
confidence: 99%
“…Details about the effect of ligand flexibility and metal type on dissociation pathways has been gathered from these studies. Additional work has also applied CID to other transition metal complexes [15][16][17][18][19][20][21][22][23][24][25][26]. In general, these studies reveal that rearrangement reactions involving the loss of small neutrals from large ligands or the loss of intact ligands from multi-ligated metal ions are typical.…”
mentioning
confidence: 99%